The Effect of Learning Media On Madrasah E-Learning Platforms On Learning Activities During The Coronavirus Disease (Covid-19) - Budiarti, Diaz; Tabroni, Imam; Fauziah, Nurul (Proceeding International Conference on Islam and Civilization (ICONIC), 2021)
The purpose of this study is to find out how the use of e-Learning Madrasah learning media affects student learning activities in SKI subjects during the Covid-19 pandemic in class XI IIS, MAN Purwakarta. The method used in this research is a quantitative correlation. The Isaac-Michael calculation determined the number of samples, and the sampling technique used was simple random sampling, which obtained a sample of 84 people from a population of 108 people. The theory used for the e-Learning Madrasah learning media variable (X) is the Rosenberg theory, while the theory used for the student learning activity variable (Y) is the learning activity theory grouped by Paul B. Diedrich. Based on the results of data analysis, it is concluded that first, the e-Learning Madrasah learning media is considered good with an average acquisition of 84.05%. Second, student learning activities are considered good, with an average acquisition of 81.87%. Third, there is a positive and significant relationship between Madrasah (X) e-Learning learning media on student learning activities (Y) in SKI subjects during the covid-19 pandemic in class XI IIS, MAN Purwakarta. Simple regression results obtained count > f table (136.114 > 3.96). It can be concluded that the alternative hypothesis, which states "there is an effect of using Madrasah e-Learning on the learning activities of class XI IIS students on SKI subjects at MAN Purwakarta during the covid-19 pandemic", is accepted and the null hypothesis which states there is no effect is rejected.